IDENTIFICATION OF LACTIC ACID BACTERIA ISOLATE 9A FROM BALI CATTLE’S COLON PHENOTYPICALLY - Ekamelinda, Mita; Suardana, I Wayan; Pinatih, Komang Januartha Putra (Buletin Veteriner Udayana; Vol. 10 No. 2 Agustus 2018DO - 10.24843/bulvet.2018.v10.i02.p14, 2018)
Lactic acid bacteria are the type of bacteria that has benefits in food and health industries as a biopreservative, fermentative, or probiotics. Bali cattle are known as potential host for specific lactic acid bacteria. The aim of this study is to identify phenotypically lactic acid bacteria 9A isolated from bali cattle’s colon, that producing a substance which known has potency as antimicrobial. In this study, phenotypic identification included conventional method and API 50 CHL. The result of this study showed that lactic acid bacteria isolate 9A was Streptococcus sp., whereas identification by kit API 50 CHL showed isolate 9A as Lactobacillus fermentum with 83% identity. The difference between the results of conventional method and kit API 50 CHL, may indicate the difference in sensitivity and specificity of the two methods, hence it needs further confirmation.